Accessibility Analysis Of Mandai Railway Station To The Transport Network In The Layout Region - Andi Hermansyah; Abdur Rahim; Zainal Muksin; Azhari Aziz Samudra; Evi Satispi (Pusat Riset dan Inovasi Nasional, 2023)
Planning the construction or development of the station needs to consider integration with environmental conditions e.g. spatial plans, land use, accessibility, distribution of the population and employment to ensure that they It would be better served by train. More in-depth studies are needed to conducted research on the characteristics of potential demand for Trans Sulawesi train users. Deep management and implementation of Accessibility Optimization to and from station access there needs to be a role of collaboration between local governments. More station area management increasing the need for cooperation of business entities, applying the concept of TOD supported by ease of regulation, and collaborative government services between the central government and local governments that synchronize policies spatial planning, transportation, and institutional implementation of TOD.